2022
DOI: 10.3389/fcvm.2022.854726
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Extracellular Vesicles From Senescent Endothelial and Vascular Smooth Muscle Cells to Vascular Calcification

Abstract: Vascular calcification is an irreversible pathological process associated with a loss of vascular wall function. This process occurs as a result of aging and age-related diseases, such as cardiovascular and chronic kidney diseases, and leads to comorbidities. During these age-related diseases, the endothelium accumulates senescent cells, which stimulate calcification in vascular smooth muscle cells. Currently, vascular calcification is a silent pathology, and there are no early diagnostic tools. Therefore, by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 115 publications
(172 reference statements)
0
8
0
Order By: Relevance
“…Vascular calcification in atherosclerosis shows a bimodal behavior in terms of risk and impact; while it has been shown that microcalcifications have a burdening effect on plaque rupture due to the low number of inflammatory cells and being more prone to rupture, higher amounts of calcification within stable plaques at various phases of atherosclerosis progression have also been found. Cellular-derived EVs from VSMCs, ECs, and platelets indisputably regulate the loss of the VSMC contractile phenotype and impact vascular calcification [ 157 , 158 , 159 ] favoring plaque calcification and atherogenesis [ 160 , 161 , 162 , 163 ]. EVs from dysfunctional endothelium [ 164 ] and senescent ECs [ 158 , 165 ] promote vascular calcification.…”
Section: Evs As Pathophysiological Drivers Of Atherothrombosismentioning
confidence: 99%
“…Vascular calcification in atherosclerosis shows a bimodal behavior in terms of risk and impact; while it has been shown that microcalcifications have a burdening effect on plaque rupture due to the low number of inflammatory cells and being more prone to rupture, higher amounts of calcification within stable plaques at various phases of atherosclerosis progression have also been found. Cellular-derived EVs from VSMCs, ECs, and platelets indisputably regulate the loss of the VSMC contractile phenotype and impact vascular calcification [ 157 , 158 , 159 ] favoring plaque calcification and atherogenesis [ 160 , 161 , 162 , 163 ]. EVs from dysfunctional endothelium [ 164 ] and senescent ECs [ 158 , 165 ] promote vascular calcification.…”
Section: Evs As Pathophysiological Drivers Of Atherothrombosismentioning
confidence: 99%
“…EVs carry cargo from the cytosol that deposits within the extracellular space. 35 The proteomics dataset showed that the upregulated proteins deposited in the ECM with Sox9 overexpression and senescence were related to EVs (Figure 8 A). We again performed comparative analysis to determine what proteins were differentially expressed between senescent control and young Sox9 overexpression ECM when both were compared independently with the young control ECM.…”
Section: Resultsmentioning
confidence: 99%
“… 64 In the pathological condition of atherosclerosis, smooth muscle cells of the cardiovascular tissue release EVs containing calcification-promoting cargo, which become risk factors for plaque formation when released into the extracellular matrix. 50 , 52 Macrophages stimulated by lipopolysaccharide during septicemia release more EVs containing proinflammatory cytokines, and this increase in cytokines in EVs is associated with the progression of myocardial dysfunction. 65 Exosomes are also involved in the transmission of some viruses.…”
Section: Characteristics Of Extracellular Vesiclesmentioning
confidence: 99%